Editorial (diségno, 2026)
The first issue of diségno, the biannual journal of the scientific society Unione Italiana per il Disegno, was published in December 2017 and continued with regular periodicity through December 2025, reaching issue no. 17. Overall, this amounts to eight years of scientific activity, during which the patient, competent, and courageous work –initially of Vito Cardone, UID President, founder of the journal and its first Editorial Director, and subsequently of Francesca Fatta, who succeeded Cardone as UID President and served as Editorial Director for two terms– together with that of the Editorial board across its three components (scientific committee, coordination, and staff), led to the online Open Access publication of 16 issues. These were characterized by diverse calls for papers and included nearly 250 articles selected through a double-blind peer review process, in addition to invited contributions. [read more]